2017
DOI: 10.1177/0269881117699616
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of medical cannabis for pharmaceutical agents for pain, anxiety, and sleep

Abstract: A prior epidemiological study identified a reduction in opioid overdose deaths in US states that legalized medical cannabis (MC). One theory to explain this phenomenon is a potential substitution effect of MC for opioids. This study evaluated whether this substitution effect of MC for opioids also applies to other psychoactive medications. New England dispensary members ( n = 1,513) completed an online survey about their medical history and MC experiences. Among respondents that regularly used opioids, over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
134
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 44 publications
15
134
1
Order By: Relevance
“…30,31 Interestingly, some studies have found that jurisdictions where cannabis is available for therapeutic purposes tend to see a decrease in prescription opioid/pain medication use, 32,33 suggesting that some people with chronic pain may be using therapeutic cannabis as a substitute for prescription opioids. 34,35 This study also indicated that among those who reported CUTP, 15.2% reported that they had medical approval to use cannabis therapeutically. Such medical approval, however, does not necessarily mean that cannabis was obtained through Health Canada's regulatory system, 6 as proof of medical authorization is required to access that system.…”
Section: Discussionmentioning
confidence: 68%
“…30,31 Interestingly, some studies have found that jurisdictions where cannabis is available for therapeutic purposes tend to see a decrease in prescription opioid/pain medication use, 32,33 suggesting that some people with chronic pain may be using therapeutic cannabis as a substitute for prescription opioids. 34,35 This study also indicated that among those who reported CUTP, 15.2% reported that they had medical approval to use cannabis therapeutically. Such medical approval, however, does not necessarily mean that cannabis was obtained through Health Canada's regulatory system, 6 as proof of medical authorization is required to access that system.…”
Section: Discussionmentioning
confidence: 68%
“…Building on previous research showing that cannabis may be an effective substitute for opioids (Hurd, 2016; Vigil et al, 2017) and other classes of prescription medications (e.g., sedatives; Piper et al, 2017; Stith et al, 2017), we provide evidence that cannabis is used to treat many different types of symptoms for which conventional pharmaceutical medications are typically prescribed, and that the magnitude of reported symptom relief and side effect profiles from using cannabis varies for people with different symptoms. The Releaf App TM users consumed cannabis to treat a wide range of health symptoms, the most frequent relating to pain, anxiety, or depression.…”
Section: Discussionmentioning
confidence: 80%
“…This population also had substantial experience with opioids so many of their MC comments were relative to these agents. Maine and Vermont, like many states, were in a high-profile opioid epidemic 21, 33 where there was a high level of concern about escalation from prescription opioids to heroin and opioid fatalities. 29 Another positive theme identified was to other medications.…”
Section: Discussionmentioning
confidence: 99%